The consumer dystopia: Hegelian-Marxist thought and late-stage capitalism - Bayford, Katherine (2024)
In a 1991 essay entitled The Antinomies of Postmodernity, Frederic Jameson wrote that it ‘seems easier for us today to imagine the thoroughgoing deterioration of the earth and of nature than the breakdown of late capitalism; and perhaps that is due to some weakness in our imagination.’ This thesis contends that it is indeed a weakness in imagination that precludes individuals - and society at large - from envisioning radically different alternatives to the status quo of late-stage capitalist society. We live in a time of ‘capitalist realism’ in which the dominating quality present within the current age severely hampers imagination and praxis alike, utopian potential is limited, and mankind is subsumed - perhaps even happily - into the apparatus of technological modernity. Few experience ‘fruitful’ alienation under such conditions. This thesis seeks to compare and analyse the thought of four key science fiction authors (Aldous Huxley, Yevgeny Zamyatin, Philip K. Dick, and Franz Kafka) with the social, economic, and cultural theory of the Frankfurt School. This work seeks to build on the output of those such as Frederic Jameson and Carl Freedman, who have drawn together shared critiques of science fiction authors and critical theorists in the past. It brings together four separate works of science fiction, spanning a transformative period of capital and its effects, with a full range of Frankfurt School thinkers operating from the early twentieth century to the present day. Nobody has yet undertaken a fullscale analysis of the similarities of thought between these two schools of thought, creating a clear comparative analysis between these specific writers and thinkers, tying this in with the context of late-stage capitalism - this work aims to fill that gap. In doing so, it seeks to argue that, for most of these thinkers, the economic and cultural apparatus at use within the twentieth and twenty-first centuries is oppressive enough that utopian possibilities become increasingly unlikely as humanity is subjected to a ‘consumer dystopia.’ Dystopian works of fiction demonstrate a critical analysis of the society in which their author lives, exaggerating certain facets and trends of those societies to highlight their characteristics. To the extent that these traits and trends are found elsewhere, dystopian works retain relevance and power for readerships in times and places other than the author’s original land. The dystopian fiction of the 20th century, often focused on the mid-to-late stage of capitalism, can accordingly transcend its age through its application to our hyper-technical, mechanised, consumerist society. The ethical and political issues addressed by these authors of dystopian literature (and the light they shed on contemporary society) are remarkably similar to discussions that have characterised the Frankfurt School of critical theory. I seek to connect these two critiques together, to showcase the synergies that exist between the various writings produced by the Frankfurt School on the one hand and the authors of these works of literature on the other. The Frankfurt School sheds a new light on these works of literature, drawing out the similarity of their critiques of contemporary consumer society in a way that nobody else has drawn attention to. This thesis is made up of six chapters. In the Theory Chapter, I give an overview of the theory utilised within this thesis, paying particular attention to the Hegelian-Marxist influence of the Frankfurt School. In the Literature Review, I look at those who have undertaken similar forms of research before, such as Carl Freedman, Darko Suvin, and Tom Moylan, and how my research builds upon (and differs from) their output. In Chapter One, I look at Aldous Huxley’s Brave New World and compare its critique of happiness, pleasure, and hedonism with that of the Frankfurt School. In the Second Chapter, I look at Yevgeny Zamyatin’s We and how it shares a critique of ‘dead’, ‘ossified’ society under capitalist conditions with the Left-Hegelian influenced Frankfurt School - and how both strands are concerned that the end of history may truly be upon us. In the Third Chapter, I look at Philip K. Dick’s Ubik, bringing together its critique of consumerism with Adorno’s theory of the Culture Industry. Chapter Four concludes with Kafka’s The Metamorphosis as a literary representation of severe alienation, and contains particular emphasis on the alienating quality of technological modernity. Each chapter brings together a particular element of Frankfurt School thought integral to the School and increasingly prevalent under latestage capitalism: compounded together, these diminish utopian possibilities whilst ostensibly increasing the standard of living for most through material goods and increased leisure. Late-stage capitalism intended to create a utopia for the consumer. Rather, these thinkers believe, it created something akin to a consumer dystopia.